Association Between Platelet Count and Grading of Esophageal Varices in Patients with Liver Cirrhosis - Afsheen Mahmood, Rozina Khan, Shaima Sultana Memon, Faiza Shaikh, Fizzah Ali, Syed Adnan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Upper GI endoscopy is the gold standard technique for diagnosing esophageal varices and to assess the risk of bleeding but is invasive in nature, costly, time consuming and burden for the department. Besides this platelet count is also an important tool to predict the esophageal varices in cirrhotic patient and it is a highly accurate test. it has been noted that platelet count in cirrhotic patients with esophageal varices, is less than 100,000/cmm but very few of the data is available so the aim of the current study was to find out the association between mean platelet count and grading of esophageal varices in patients with liver cirrhosis. Methods: A descriptive cross-sectional study was conducted at the medicine department of Jinnah Postgraduate Medical Center (JPMC), Karachi. For testing platelet count the blood sample was sent to the pathology laboratory of the hospital. Gastroenterologist performed the upper gastrointestinal endoscopy to grade the esophageal varices. Data was analyzed by using the Statistical Package for Social Science (SPSS) version-20. ANOVA with Post-Hoc Tuckey test was applied to find out the correlation between the variables. p-value less than 0.05 was considered as significant. Results: The mean age of the study participants was 34.9±8.6 years. Majority of the study participants were male (61.1%) as compared to their counterparts. The mean platelet count among the study participants was 113,200±29000 /u L majority of cirrhotic patients included in the study were having grade III of esophageal varices (39.5%). It has been noted that mean platelet count decreased with increasing grade of esophageal varices and the association was significant. Cirrhotic patients having Grade I esophageal varices were having near normal mean platelet count but those who were in Grade V of esophageal varices, having markedly decreased platelet count as compared to Grade I, II, III and IV. Conclusion: It can be concluded that the mean platelet count is significantly inverse association with the grading of esophageal varices, as low as the platelet count, worst the esophageal varices in patients with liver cirrhosis. So testing mean platelet count can be used for screening purpose of esophageal varices as it is a cost effective test. Keywords: Cirrhosis, Esophageal varices, Mean Platelet count,